Influence of zinc oxide quantum dots in the antibacterial activity and cytotoxicity of an experimental adhesive resin. (June 2018) - Garcia, Isadora Martini; Leitune, Vicente Castelo Branco; Visioli, Fernanda; Samuel, Susana Maria Werner; Collares, Fabrício Mezzomo
Abstract: Objective: To evaluate the influence of zinc oxide quantum dots (ZnOQDs ) into an experimental adhesive resin regarding the antibacterial activity against Streptococcus mutans and the cytotoxicity against pulp fibroblasts. Materials and methods: ZnOQDs were synthesized by sol-gel process and were incorporated into 2-hydroxyethyl methacrylate (HEMA). An experimental adhesive resin was formulated by mixing 66.6 wt.% bisphenol A glycol dimethacrylate (BisGMA) and 33.3 wt.% HEMA with a photoinitiator system as control group. HEMA containing ZnOQDs was used for test group formulation. For the antibacterial activity assay, a direct contact inhibition evaluation was performed with biofilm of Streptococcus mutans (NCTC 10449). The cytotoxicity assay was performed by Sulforhodamine B (SRB) colorimetric assay for cell density determination using pulp fibroblasts. Data were analyzed by Student's t -test (α = 0.05). Results: The antibacterial activity assay indicated statistically significant difference between the groups (p = 0.003), with higher values of biofilm formation on the polymerized samples of control group and a reduction of more than 50% of biofilm formation on ZnOQDs group. No difference of pulp fibroblasts viability was found between the adhesives (p = 0.482). Conclusion: ZnOQDs provided antibacterial activity when doped into an experimental adhesive resin without cytotoxic effect for pulp fibroblasts. Thus, the use of ZnOQDs is a strategy to develop antibiofilm restorative polymers with non-agglomerated nanofillers. Clinical significance: ZnOQDs are non-agglomerated nanoscale fillers for dental resins and may be a strategy to reduce biofilm formation at dentin/restoration interface with no cytotoxicity for pulp fibroblasts.